(untitled) (Bangladesh Veterinarian, 2011)
The effects of oral administration of seven mL soybeen oil/kg live weight (LW) on the performance and carcass characteristics of native ram. In a 162 days feeding trial, 18 growing native rams (9.4 ± 1.2 kg BW and 176 ± 5.6 d of age) were randomly allocated to three treatments (T0, control, T1, monthly infusion of oil and T2, fortnightly oil infusion group) with six replicates in each. All animals were fed roughage (Ad lib urea molasses straw, UMS) and concentrate (1.5% of body weight). After feeding and digestion trial, five animals in each group were slaughtered for carcass characteristics. During the trial, growth rate was significantly (P<0.05) influenced by the treatments (T0, T1 and T2 were 69.5, 83.8 and 69.8 g/d). On average, T1 group showed 20.7% higher growth over the control and T1. The protozoa populations were reduced by 74% and 84% in T1 and T2 than that of control group. Consequently, the ammonia concentration in the rumen fluid of T1 group was significantly (P<0.05) lower (177 mg/L) than that of T2 (208.0 mg/L) and control (245.0 mg/L) group, respectively. Consequently, Feed conversion ratio (FCR) was better (8.0) belonged to T1 than that of control (8.6) and T2 (9.3). Interestingly, fat deposition was inclined significantly (P<0.05) in T2 group than that of T1 and control, which is unacceptable to the customers. Meanwhile, fortnightly oil treatment (T2) is not recommended, but further study is required with different intervals. DOI: http://dx.doi.org/10.3329/bvet.v28i1.8810 Bangl. vet. 2011. Vol. 28, No. 1, 19-30